Properties of the light emitted by a silicon on-chip optical parametric oscillator (OPO). - Arciniegas, Carlos Andres Gonzalez (2017)
The Optical Parametric Oscillator (OPO) has been one of the most versatile source of non-classical states of light. Usual configurations of such devices are a macroscopic second order nonlinear crystals inside an optical cavity. Recently the use of silicon photonics techniques allowed the implementation of high quality factor microcavities and OPOs which include several technological advantages over usual configuration as a small size, bigger bandwidth, CMOS compatibility, facility to engineer the dispersion properties and compatibility with commercial optical fiber communications. Nevertheless the nonlinearity present within these systems is a third order nonlinearity for which theoretical calculations lack in the literature. Here we describe theoretically the quantum properties of the light generated in an OPO with a third order nonlinearity. We showed that the effects of phase modulation (which are not present in the second order nonlinearity) and dispersion are determinant in the way that oscillation and entanglement is produced in the system. Despite of these effects, bipartite and tripartite entanglement is predicted with the use of the Schmidt modes formalism. We also describe the system when there are more modes exited within the cavity and a frequency comb is formed. In such a situation, using again the Schmidt modes formalism, multipartite entanglement was predicted as well.